Comparative genome analysis of Solanum lycopersicum and Solanum tuberosum - Lall, Rohit (Biomedical Informatics, 2013)
Solanum lycopersicum and Solanum tuberosum are agriculturally important crop species as they are rich sources of starch, protein, antioxidants, lycopene, beta-carotene, vitamin C, and fiber. The genomes of S. lycopersicum and S. tuberosum are currently available. However the linear strings of nucleotides that together comprise a genome sequence are of limited significance by themselves. Computational and bioinformatics approaches can be used to exploit the genomes for fundamental research for improving their varieties. The comparative genome analysis, Pfam analysis of predicted reviewed paralogous proteins was performed. It was found that S. lycopersicum proteins belong to more families, domains and clans in comparison with S. tuberosum. It was also found that mostly intergenic regions are conserved in two genomes followed by exons, intron and UTR. This can be exploited to predict regions between genomes that are similar to each other and to study the evolutionary relationship between two genomes, leading towards the development of disease resistance, stress tolerance and improved varieties of tomato.